A COMPARATIVE STUDY OF SLANG USAGE IN ENGLISH AND UZBEK YOUTH SPEECH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study investigates the use of slang among English and Uzbek youth, examining linguistic characteristics, social functions, and cultural implications. Slang acts as a marker of identity, group affiliation, and creativity in communication . Comparative analysis shows that while English slang evolves rapidly through digital media, Uzbek slang integrates traditional expressions with modern borrowings and neologisms. The findings highlight the importance of understanding youth slang for sociolinguistic research and language education .